Analisis Pengendalian Kualitas Produksi Roti UMKM Menggunakan Seven Tools dan 5W+1H untuk Menurunkan Tingkat Kecacatan - Moh. Ririn Rosyidi; Narto Narto; Nailul Izzah; Anik Rufaidah (JiTEKH, 2026)
Quality control in bakery MSMEs still has defects and inconsistencies in food quality in the production process. The defect rate reached 17.3% (3,474 units out of 20,085 production), dominated by unrisen bread (53.1%) and burnt bread (46.9%), with the production process not statistically controlled (11 points outside the control limits; CL=0.1730; UCL=0.2122; LCL=0.1337). This study aims to identify the root causes of defects through the 4M approach and formulate recommendations for structured, measurable, and sustainable improvements. The main contribution of the research is to develop a proactive, data-based quality control system with the integration of Seven Tools and 5W+1H, which was previously only descriptive-diagnostic. Proactive management is realized through the determination of critical parameters before production by paying attention to the final mixing dough temperature of 26°C, mixing duration of 12 minutes (standard deviation <1 minute), first fermentation of 50 minutes, final proof of 45 minutes in the proofer (temperature 36°C), oven temperature of 185±2°C, preheating of 10 minutes, sugar content of 10% of the flour weight (tolerance of ±1 gram), minimum dough thickness of 1.2 cm and digital scales. Specific suggestions such as monthly oven calibration (deviation ≤±5°C), replacement of black pans with silver aluminum (heat absorption -25%), and standardization of baking time of 18 minutes with an alarm, are proven to be able to change the quality control strategy of MSMEs from final inspection (reactive) to continuous statistical process control (proactive). After the implementation of the proposed improvements, the control chart showed 13 data points were within the control limits (UCL=0.2122; LCL=0.1337), which indicated the production process was statistically under control with significant stability improvement, the target was to reduce the total defect rate from 17.3% to ≤9% with good planning.